Pengembangan Materi Basic English Berbasis Pariwisata Untuk Program Studi Bahasa Asing Terapan Konsentrasi Bahasa Jepang - Lenggahing Asri Dwi Eko Saputri (KIRYOKU, 2020)
In 2019, Vocational School  Diponegoro University opened several new study programs. One of them is Applied Foreign Language Program. This study program has 2 majors namely English and Japanese. In the third semester, students are directed to take one of the majors based on their interests and talents. Although they have chosen their major that can be English or Japanese, they still have to study both of them. For 3rd semester students of Japanese major, they are also required to take Basic English courses. This course itself will be based on tourism in accordance with the vision of the Applied Foreign Language program that is not only to give the students the competence of mastering English and Japanese languages but also give them the competence of tourism and hospitality. The aim of this research is to develop Tourism based Basic English material for Japanese major of Applied Foreign Language program. The method used in this research is Research and Development while the model that researchers use is ADDIE model (Analysis-Design-Develop-Implement-Evaluate). The result of this research is Tourism based Basic English material for Japanese major of Applied Foreign Language program which consists of four tourism themes namely An Introduction to Travel and Tourism, Tourism Organisations, Promotion and Marketing and Types of Transport and Accommodation. Those themes will be discussed in four integrated English skills which include listening activity, speaking activity, reading activity and activity writing.